Design insights for socially-led interventions. (1st March 2019) - Phillips, Robert
Design has become an accessible tool for organizations to create impactful outputs. These topics have diverged from mere retail to include: economic prospects, technological paradigms, social empowerment, sustainable resources, citizen-led opportunities and challenges that cross demographics, societies and cultures. Accessible technologies and the reduction of barriers to pilot funding have (in part) enabled the advancement of these socially-led responses through design. 'Enablers' take many forms including: digital manufacturing, accessible hardware, design platforms and smart technologies, all challenging what 'designed products' are as the 'product' is a social impact or intervention. The work mines embedded knowledge from successful award-winning organizations, which have not publically shared their unique insights. The work analyses an interview series of 60 plus CEOs, founders and co-founders of socially-led organizations with both design and non-design origins. The work identifies socially-led design 'architectures', highlighting issues, lessons and transferable insights. The study includes global organizations occupying territories of: not-for-profits, commercial practices, grass roots organizations, science practitioners, community-led ventures and intellectual property enterprises, selected from leading awards. The article identifies insights leading towards 'socially-led product architecture', and repeatable lessons, for non-design and design audiences.